Prevalence of Primary Types of Headache and Its Impact on Daily Life in Health Care Professionals in a Tertiary Care Health Institution - Kainat Amjad, Afrah Mudassir, Husnain Hashim, Maria Sattar, Danial Bajwa, Muhammad Arif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Headache is characterized by the painful and disabling disorder of the central nervous system CNS. The most common symptoms experienced by the person suffering from the headache are pain in head, neck and face. Objective: This study aims to assess the prevalence of primary types of headaches, knowledge of their types, their impact on the productivity and work efficiency of the healthcare professionals in a tertiary care health institution. Study design: This cross sectional study was conducted at Neurology Department, Fauji Foundation Hospital, Rawalpindi for duration of 1 year from December 2020 to December 2021. Material and Methods: An estimated number of 1000 adult healthcare professionals aged above 18 were included in this research. Simple convenience sampling technique was used for sampling. According to the Inclusion criteria the individual should be an adult healthcare professional. According to the exclusion criteria Individuals below the age of 18, not a part of the tertiary care hospital were excluded. Data was collected through using a structured questionnaire comprised of three sections. Results: To proceed with this study, 1000 healthcare professionals were selected for this survey. The participants submitted questionnaires. The respondents include 440 doctors and 560 nurses. Their age was from 20 to 60 years. The ages of the doctors were above thirty and the age of the nurses was above 25 years. Among them, 6 participants were identified with two basic types of primary headache, and 36 were suffering from other kinds of issues like CDH, neuralgia, and unknown types of headache. Only two nurses were suffering from MOH. Sleep patterns also play role in headache disorders. Conclusion: This study predicted that the probability of primary headache issues is greater in medical care professionals as compared to the general public. Both nurses and doctors are more prevalent to headache issues. Multiple factors are linked with the prevalence of headache issues i.e. gender, age, sleep patterns, and night shifts. These factors may lead to migraine and TTH. For the welfare of health of medical professionals, there is a need for awareness related to different health issues and all the factors causing headache disorders. Keywords: Headache disorders, neuralgia, Sleep patterns, and primary headache.